(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This article is the result of the inter-institutional research proposal Schools of Arts and Crafts in Brazil: history, training proposals and continuities in the formation of the Bachelor of Fashion Design. The adapted approach is that of historiography and reflects on the practices of the handloom in the city of Carmo do Rio Claro and on how its language is absorbed by the fashion world. Through the understanding of its formative origin, we seek to reflect and understand how these practices were passed and sedimented through time and in the face of social and economic transformations. For this, we reflect on its shekels and its agents that in one way or another contributed to its maintenance and to the maintenance of its fundamental knowledge.